Development and characterization of essential oils incorporated carrageenan based edible film for packaging of chicken patties. Issue 1 (8th February 2016) - Soni, Arvind; Kandeepan, G; Mendiratta, S. K.; Shukla, Vivek; Kumar, Ashish
Abstract : Purpose: – The purpose of this paper was to develop an antimicrobial edible film coated with essential oils for packaging application with characterization of its physicochemical properties. Livestock products especially meat products need special packaging system for protection. The most well-known packaging materials are polyethylene or co-polymer-based materials which have led to serious ecological problems due to their non-biodegradability and non-renewable nature. There has been a growing interest for edible films in recent years trying to reduce the amount of wastes, capable of protecting the food once the primary packaging is open, and because of public concerns about environmental protection. Various kinds of antimicrobial substances can also be incorporated into edible films to improve their functionality, as these substances could limit or prevent microbial growth on food surface. Design/methodology/approach: – Biopolymers such as carrageenan and carboxymethylcellulose and their various combinations were tried to develop an edible film. The levels of antimicrobial substances such as oregano and thyme essential oils were standardized on the basis of their minimal inhibitory concentration against Escherichia coli, Salmonella pullorum, Staphylococcus aureus and Listeria monocytogenes . Standardized edible film coated with standardized concentration of essential oil was examined for different physicochemical properties and compared with edible film without essential oil. Findings: – In total, 1.5 per cent (w/v) solution of carrageenan was found best suited biopolymer for edible film formation on the basis of thickness, transparency and elongation ability. Combined concentration of oregano (0.02 per cent) and thyme (0.03 per cent) essential oils were found to be best suited for coating the edible film as antimicrobial application. Research limitations/implications: – Future research may benefit from the present attempt in evaluating the potency of easily available agricultural by produces for preparation of economically viable edible film incorporated with various natural biopreservatives in combination for the enhancement of shelf life. Originality/value: – Antimicrobial packaging for enhancing the quality and shelf life of stored meat products offers great scope for further research in this field. Moreover, the literature pertaining to the application of edible films containing biopreservative for chicken meat products is very limited.